Parental satisfaction towards care given at neonatal intensive care unit in Ethiopia: A systematic review and meta-analysis. - Teklehaimanot Gereziher Haile; Gebreamlak Gebremedhn Gebremeskel; Teklewoini Mariye; Guesh Mebrahtom; Woldu Aberhe; Abrha Hailay; Teklehaymanot Huluf Abraha; Negasi Asres; Teklay Guesh; Girmay Teklay (PLoS ONE)
Background Satisfaction reflects a consumer's judgment regarding the quality of care received. Satisfaction of parents with healthcare services can serve as a reliable indicator for evaluating the quality of care given to their newborns. The aim of this study is to determine the pooled prevalence of parental satisfaction with neonatal intensive care unit services and its associated factors in Ethiopia. Methods International databases such as PubMed/Medline, African Journals Online, SCOPUS, Web of Science, and Google Scholar were used to identify relevant published articles. Risk of bias was assessed independently by two authors. Funnel plot and Egger regression test were also employed to assess publication bias. A significant p-value of 0.05 or less suggests the presence of publication bias. PROSPERO registration number is CRD42024570971. Results The researchers initially identified a total of 1,264 articles through their search strategy from all databases. Finally, eleven studies met the inclusion criteria and were considered suitable for the final meta-analysis. The pooled prevalence of parental satisfaction with neonatal intensive care unit services in Ethiopia was 55% (95% CI: 49%-60%). There was neither publication bias nor small study impact among the included studies. Based on the subgroup analysis by region, the pooled prevalence in Oromia were slightly higher, 63% (95% CI: 57%-69%). Birth weight, length of hospital stays, place of residence, and availability of necessary information are factors identified as significant predictors for parental satisfaction with neonatal intensive care unit service. Conclusion According to the study's findings, there is a lower pooled prevalence of parental satisfaction than in previous research that was published in some countries. By working to raise the satisfaction levels of parents in neonatal intensive care units, healthcare facilities can enhance the overall experience for both parents and infants, leading to improved outcomes and a more positive care environment.